Potential shifts in olive flowering according to climate variations in Southern Italy. (27th March 2012) - Orlandi, F.; Avolio, E.; Bonofiglio, T.; Federico, S.; Romano, B.; Fornaciari, M.
ABSTRACT Phenological investigations that adopt aerobiological monitoring methodologies are frequently used for species that rely on the wind for pollen grain dispersion, such as the olive in the Mediterranean basin. The present study of olive flowering dates was carried out in the Calabria region (southern Italy). These were calculated on the basis of a phenological study of pollen levels in the atmosphere in three typical olive‐growing areas over an 11 year study period (1999–2009). This phenological method provides olive flowering maps that are based on temperatures (as the growing degree days: GDDs), which are highly correlated with the release of the pollen grains. According to the model developed, the average GDDs corresponding to the flowering dates were calculated for the baseline period of 1981–2000. Moreover, with the use of meteorological data derived from the Intergovernmental Panel on Climate Change scenarios, the future olive flowering dates are estimated for the 20 year period from 2081 to 2100. The close relationships between the spring temperature trends and the reproductive phenological phases in the olive are highly sensitive to climatic change, which has implications in terms of potential latitude and altitude shifts in the olive cultivation areas. In some cultivation areas in southern Italy, the present particular combination of microclimate, soil status and level of erosion is considered as limiting to regular vegetative plant development. However, the use of olive cultivars that are specifically adapted to extremely stressful environments, in terms of high temperatures and water deficit, might represent the main solution for the mitigation of the consequences of climatic change.